1977
DOI: 10.1063/1.323391
|View full text |Cite
|
Sign up to set email alerts
|

The physics of zinc oxide varistors

Abstract: This paper presents a physical description of the action of ZnO varistors, which are complex ceramic bodies of ZnO grains sintered in an oxide flux; their conductivity is very low at low voltage, but becomes high after a certain breakdown voltage is reached. It is found that depletion layers in the ZnO adjacent to the intergranular layers of oxide flux are the principal barrier to conduction at low voltage. These depletion layers are formed because electron traps in the intergranular layer absorb electrons fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1
4

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(76 citation statements)
references
References 10 publications
0
71
1
4
Order By: Relevance
“…Contrary to the observations in this study and for the varistor materials just cited, it has also been observed by other investigators that the resistivity of single crystal ZnO decreases upon being doped with Co [42]; however, the experimental procedure and the Co doping concentration were not specified.…”
Section: Co/cco+zn] (Atom X>contrasting
confidence: 99%
“…Contrary to the observations in this study and for the varistor materials just cited, it has also been observed by other investigators that the resistivity of single crystal ZnO decreases upon being doped with Co [42]; however, the experimental procedure and the Co doping concentration were not specified.…”
Section: Co/cco+zn] (Atom X>contrasting
confidence: 99%
“…The decrease in the activation energy with an increase in dc-biasing is associated with the reduction in the potential energy height of Schottky barrier. The reduction in potential energy of Schottky barriers leads to the increase in width of depletion zone, which results in the decrease in the capacitance of grain boundary [28,[30][31][32][33][34][35][36][37]. This effect is seen in Fig.…”
Section: Structural Analysismentioning
confidence: 92%
“…This elec-tron transfer, followed by considerable orbital rehybridization within the valence band at the O,:ZnO interface, results in an empty conduction band and partially occupied 0 r*-like states coinciding with the top of the valence band. 4 The latter states are represented by the 9e ,orbital of the model o ZnO -cluster in Fig. l(b) having the orbital topology shown in Fig.…”
Section: Preliminary Theoretical Modelmentioning
confidence: 99%
“…Recent high resolution transmission electron microscopy [2] shows, however, this not to be the case. Although a considerable number of alternative models have been proposed in recent years [3,4] they all propose in common the existence of a charged grain boundary interface bounded by space charge layers penetrating into the adjoining grains. All models either implicitly or explicitly rely on the existence of low-lying interface states or traps at the intergranular layers to proyide for the formation of the potential barrier at the grain/grain-boundary interface.…”
Section: Introductionmentioning
confidence: 99%